Comparative global knowledge about the use of digital technologies for learning among young children - LIVINGSTONE, Sonia (Institutional Knowledge at Singapore Management University, 2019)
This chapter focuses on the challenge of examining the conditions and consequences of young children’s digital technology practices with a global focus. By far the majority of the available research derives from the world’s wealthier countries, but it is in the global South that the majority of children – including child internet users live and, notably, where the majority of future users will live. Enthusiasm and motivation, interactivity with toys and devices, cooperation among peers, parents and teachers – all of these explain why digital technologies can serve as a “catalytic change agent” for very young children. Strongly influenced by Confucianism, Chinese children are traditionally expected to respect parents’ authority, while Chinese parents are responsible for their children’s moral development. With speculation rife that the pace of global internet and mobile adoption continually outstrips the capacity of parents, educators or governments to provide for children’s wellbeing in the digital environment, the paucity of sound research is problematic.